Playing catch-up: Vietnamese rural student voices on bridging academic marginalization - Cong Vu, Danh; Thanh Nguyen, Phuong (International Journal of Evaluation and Research in Education (IJERE), 2025)
The increasing adoption of English as the instructional language in Vietnamese higher education has created significant learning barriers for rural students. Their under-resourced schools and a communicative English-neglected curriculum provided limited foundations prior to engaging in lectures, presentations, and discussions now conducted exclusively in academic English. Rural students often face significant challenges when transitioning into this demanding academic environment due to their limited prior exposure to English and the disparities in educational resources between rural and urban areas, yet there is limited understanding of their experiences and coping mechanisms. This study examines the challenges faced by rural Vietnamese undergraduate English majors and investigates their coping strategies in achieving academic competency. Using semi-structured interviews, this case study investigated three Vietnamese undergraduate English majors from low-income, rural backgrounds at an urban university. The findings revealed two key dimensions: i) participants initially experienced significant challenges including skill deficits across all language domains and identity struggles manifesting as feelings of inadequacy and isolation and ii) students developed a comprehensive set of coping strategies encompassing language learning, social support, and psychological adaptation. The study highlights the necessity of implementing multi-dimensional support systems that address not only language learning but also social and psychological aspects of academic adaptation. Such comprehensive support, through precision language education, can promote more equitable access and inclusion in language education.